2020
DOI: 10.7150/jca.39511
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Enhances Radiosensitization of Nasopharyngeal Carcinoma via Mediating Regulation of Tumor Stem-like Cells by a CircRNA Network

Abstract: Circular RNAs (circRNAs) are involved in cancer development via inhibition of miRNAs, which are associated with differentiation, proliferation, migration, and carcinogenicity. Curcumin has antioxidant and anti-cancer properties, and it has also been used as a radiosensitizer. In this study, we explored the potential relationships among curcumin, circRNAs, and nasopharyngeal carcinoma (NPC). We compared the differences in circRNA levels in NPC cell lines after radiotherapy and after treatment with curcumin, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…24 Has_circRNA_006660 was upregulated and sponged miR-1276 to increase the radiation sensitivity in nasopharyngeal carcinoma. 25 The effect of circRNAs dysregulation on the radiation sensitivity of cancers remained disunited; however, the upregulation of circ_0062020 further contributed to the facilitation of radiation sensitivity in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…24 Has_circRNA_006660 was upregulated and sponged miR-1276 to increase the radiation sensitivity in nasopharyngeal carcinoma. 25 The effect of circRNAs dysregulation on the radiation sensitivity of cancers remained disunited; however, the upregulation of circ_0062020 further contributed to the facilitation of radiation sensitivity in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent research on NPC has indicated that miR-335 is downregulated in NPC tissues. 24 Zhou et al, 25 showed that decrease in miR-335 level inhibits the proliferation and metastasis of NPC cells through TRIM29. Our experiments demonstrate that the miR-335 inhibitor partly counteracts the suppressive effect of si-ZNRD1-AS1 on cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A study compared the differences in circRNA levels in NPC cell lines after radiotherapy and after treatment with curcumin, using a high-throughput microarray. Finally, it was demonstrated by reverse transcription-quantitative polymerase chain reaction assay and wound healing assay that curcumin could enhance radiosensitization of NPC cell lines via mediating regulation of tumor stem-like cells by the “hsa_circRNA_102115”-“hsa-miR-335-3p”-“MAPK1” interaction network ( 115 ). At present, although circRNA has shown significant activity in the treatment of cancer, there are few reports on the regulation of circRNA by Active Ingredients of Chinese Medicine, which is also an important direction for future researchers to concern and research.…”
Section: Regulation Of the Anti-tumor Mechanism By Circrna And Other mentioning
confidence: 99%